Imagined contact theory : a study of the relationship between the use of weibo and perceived discrimination amongst chinese immigrants in Singapore. - Chia, Alvin Zhao Yuan. (2013)
Immigration has evolved to be a controversial issue in Singapore in recent years, with foreigners making up 40.7% of the population. In particular, Chinese immigrants have been the subject of scorn and hostility, as they are perceived as threats who dilute national identity and competitors for jobs. The locals feel that the Chinese have values and norms alien to them. For instance, they are perceived to be loud, uncouth and socially aggressive by locals. Such stereotypes lead to tensions that often play out online, hampering effective interaction which would facilitate their eventual integration into the community. This study examined how virtual contact through mediated communication using the social networking site (SNS) Sina Weibo can reduce how Chinese in Singapore perceived themselves as being discriminated by the locals. It has been suggested that computer-mediated communication (CMC) offers the potential for parties to interact with reduced anxiety. The four variables studied were: Contact, virtual contact, perceived discrimination and integration into the host society. As part of the research, a five-week campaign sought to engage young Chinese immigrants aged 16 to 35 living in Singapore. Using the transtheoretical model of behavioural change, the campaign sought to promote an open discussion of issues that would prepare them for future contact. Results were triangulated using both quantitative and qualitative methods, revealing that virtual contact was a first step in encouraging positive interactions between the two groups. The findings were discussed in relation to the specific recommendations that can be made at governmental and institutional levels.